The PIN1–p38–CtIP signalling axis protects stalled replication forks from deleterious degradation - Vivalda, Francesca; Gatti, Marco; Manfredi, Letizia; Dogan, Hülya; Porro, Antonio; Collotta, Giulio; Ceppi, Ilaria; von Aesch, Christine; van Ackeren, Vanessa; Wild, Sebastian; Steger, Martin; Canovas, Begoña; et al. (Nucleic acids research, 2025)
Abstract Human CtIP plays a critical role in homologous recombination (HR) by promoting the resection of DNA double-strand breaks. Moreover, CtIP maintains genome stability through protecting stalled replication forks from nucleolytic degradation. However, the upstream signalling mechanisms governing the molecular switch between these two CtIP-dependent processes remain largely elusive. Here, we show that phosphorylation of CtIP by the p38α stress kinase and subsequent PIN1-mediated CtIP cis-to-trans isomerization is required for fork stabilization but dispensable for HR. We found that stalled forks are degraded in cells expressing non-phosphorylatable CtIP or lacking PIN1–p38α activity, while expression of a CtIP trans-locked mutant overcomes the requirement for PIN1–p38α in fork protection. We further reveal that Brca1-deficient mammary tumour cells that have acquired PARP inhibitor (PARPi) resistance regain chemosensitivity after PIN1 or p38α inhibition. Collectively, our findings identify the PIN1–p38–CtIP signalling pathway as a critical regulator of replication fork integrity. Graphical Abstract Graphical Abstract